Exploring the genetic basis of pre-harvest sprouting in rice through a genome-wide association study-based haplotype analysis - Myeong-Hyeon Min; Aye Aye Khaing; Sang-Ho Chu; Bhagwat Nawade; Yong-Jin Park (Journal of Integrative Agriculture, 2024)
Pre-harvest sprouting (PHS) poses a significant global challenge to cereal production, impacting both yield and quality. In this study, we employed genome-wide association studies (GWAS) on diverse rice accessions to identify novel PHS-associated haplotypes. An assessment of 127 cultivated accessions for panicle germination (PHS) and detached grain germination (germination rate of detached grains at the 14th day (D14)) revealed considerable phenotypic variation among rice ecotypes. GWAS analysis identified 91 significant signals at –log10(P-value)>5, including 15 SNPs for PHS and 76 SNPs for D14. A subsequent linkage disequilibrium (LD) block-based GWAS analysis detected 227 significant SNPs for both traits, consisting of 18 nonsynonymous substitutions located on the coding regions of nine genes. Further haplotype analysis identified 32 haplotypes, with 10 specific to cultivated accessions, 19 specific to the wild type, and three shared between them. A phenotypic assessment of major haplotypes revealed significant differences between resistant (Hap1 and Hap2) and susceptible haplotypes (Hap5, Hap27, and Hap28), distinguished by a G/A SNP within a novel gene, Os04g0545200. The identified haplotypes offer promising prospects for haplotype-based breeding aimed at enhancing PHS resistance in rice.